Microhardness and brittle strength of ZnSe₍₁₋ₓ₎Teₓ crystals grown from melt - Rybalka, I.A.; Galkin, S.N.; Voronkin, E.F.; Ryzhikov, V.D.; Mateychenko, P.V. (Functional Materials, 2006)
Mechanical properties of ZnSe₍₁₋ₓ₎Teₓ solid solutions (0 < CTe < 1.3 mass % ) have been studied using indentation method in two modes (indenting and scratching). The breaking limits for doped and undoped crystals have been measured by uniaxial compression. For the crystals where the dopant concentration CTe≈0.3 %, the microhardness anisotropy coefficient is equal to unity. This can be explained by disappearance of stacking defects in the crystals at the mentioned tellurium concentration due to favorable conditions for the sphalerite structure in the solid solution. As the Te concentration in the solid solution varies within the 0.2 to 1.3 % range, the crystal microhardness has been shown to increase linearly by 23 %. The fact has been confirmed by measuring the brittle fracture limit for Te doped and undoped ZnSe crystals. The fact can be explained by local distortions of ZnSe lattice due to Te atoms present and by the dislocation mobility decrease associated thereto, the combination of both factors results in the material strengthening. Effect of heat treatment and the block boundaries on the strength limit and cracking resistance of ZnSe₍₁₋ₓ₎Teₓ crystals has been established that is of importance when the material is subjected to machining.